Nilai Pendidikan Karakter Tokoh Prabu Kresna dalam Serat Pedhalangan Lampahan Tunggul Wulung Pathet Nem untuk Siswa Sekolah Dasar - Fitriana, Tya Resta; Verrysaputro, Exwan Andriyan (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2021)
This study aims to describe the character of the Prabu Kresna character in Serat Pedhalangan Lampahan Tunggul Wulung on the scene in pathet nem. This lampahan tells the story of King Kresna who is a king in the Dwarawati Kingdom. Serat Pedhalangan Lampahan Tunggul Wulung is interesting to study because there are many values ​​of character education that can be translated into education. The author of this study will focus on exemplary methods to develop character in elementary school children. This exemplary method can be implemented in teaching and learning activities in class. King Kresna is the focus of this study because he is a depiction of a wise king. This exemplary method will be integrated into Javanese language subjects, especially puppet material. The data in this study are dialogues, monologues, sentences, and narratives of Prabu Kresna's character who show character education. The data analysis technique of this research is a documentation study technique. The approach used in this research is descriptive qualitative. The results of the study show that Prabu Kresna shows a character that can be used as guidance in the Tunggul Wulung Lightning Pedhalangan 1) respect for others; 2) nationalism; 3) religion and 4) leadership.